VALIDATION OF THE HYBRID METHOD FOR NEAR LIGHTING ELECTROMAGNETIC FIELD CALCULATION TAKING INTO ACCOUNT THE CONDUCTIVITY OF THE SOIL - M'ZIOU, N.; MOKHNACHE, L.; BOUBAKEUR3, A. (Courrier du Savoir; Vol. 11 (2011): Courrier du Savoir)
In this paper we propose a hybrid method for evaluating the electromagnetic field radiated by lightning taking into account the effect of the conductivity of the soil. The proposed method is the combination of the images method and finite difference time-domain (FDTD) method. The magnetic field is obtained by the use of the images theory and the electric field is solved with using FDTD method. We calculate first, the electromagnetic field with supposing the ground as a perfect conductor and secondly we introduce the effect of the conductivity of the soil by the use of approximations formula.